The long dispute for the common and solidary in the economy (towards a more plural order) (Cultura Económica, 2019)
This article presents relevant background concerning the origins, historical inspirations, content and contemporary challenges of economic practices conceptualized as constituents of a Social and Solidarity Economy (SSE). We will consider, in this regard, what it means to introduce the social in the economic. We will propose that an SSE can be understood as a way of understanding, and building on, the overlap between the social and the economic from an emancipatory perspective. A central focus will be on the kinds of social relationships that SSE generates in its characteristic production practices.   Further, these same considerations lead to highlighting the potential of an SSE to enhance the prospects for economic democracy, due to the expansion of the scope of common property that it entails.  Consequently, by the same token, it strengthens political democracy and enhances the prospects for extending the scope of political democracy.
Keywords: SOLIDARITY ECONOMY; COMMUNITY; COMMON GOODS; ECONOMIC DEMOCRACY; MARKET